2010
DOI: 10.1371/journal.pone.0013938
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of a Pathogen: The Mycobacterium tuberculosis Proteome In Vivo

Abstract: Background Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is a facultative intracellular pathogen that can persist within the host. The bacteria are thought to be in a state of reduced replication and metabolism as part of the chronic lung infection. Many in vitro studies have dissected the hypothesized environment within the infected lung, defining the bacterial response to pH, starvation and hypoxia. While these experiments have afforded great insight, the picture remains incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 68 publications
11
165
1
Order By: Relevance
“…As such, members of the PE/PPE family of proteins may play subtly different functional roles and are required at different stages of disease. PPE38 was identified as one of the most highly expressed proteins of M. tuberculosis after a 90-day infection of guinea pig, suggesting that PPE38 plays a potentially critical role in persistent infection (43). This is in accor- dance with our finding that PPE38 plays a role in the virulence of M. marinum.…”
Section: Discussionsupporting
confidence: 84%
“…As such, members of the PE/PPE family of proteins may play subtly different functional roles and are required at different stages of disease. PPE38 was identified as one of the most highly expressed proteins of M. tuberculosis after a 90-day infection of guinea pig, suggesting that PPE38 plays a potentially critical role in persistent infection (43). This is in accor- dance with our finding that PPE38 plays a role in the virulence of M. marinum.…”
Section: Discussionsupporting
confidence: 84%
“…A subsequent literature search revealed that almost all further selected IVE-TB proteins (14 of the 16) have been identified previously in M. tuberculosis proteomic studies, confirming the protein expression of the M. tuberculosis genes identified in our study (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) (Table III). Indeed, we observed that M. tuberculosis- FIGURE 3.…”
Section: Immunogenicity Of Newly Identified Ive-tb Agssupporting
confidence: 87%
“…The detection of NarG, NarH, and FdhF in guinea pigs during pulmonary infection (33) confirms that these proteins are expressed by M. tuberculosis in this animal model (32). Drug treatment of guinea pigs infected with M. tuberculosis results in the resolution of secondary lesions but has a reduced effect on primary lesions, where some bacteria are found in the necrotic zone, and the majority of the persisting organisms are located in the acellular rim of the lesion (34).…”
Section: Discussionsupporting
confidence: 56%